Crigler Najjar Syndrome Type 2: a Case of Unexplained Jaundice in an Adult (Faridpur Medical College Journal, 2020)
Crigler-Najjar Syndrome (CNS) type 2 is a rare genetic disorder which is characterized by non-hemolytic unconjugated hyperbilirubinaemia. It is caused by defect in bilirubin conjugation due to complete or partial deficiency of uridine 5'-diphosphate-glucuronosyltransferase (UGT). Affected individuals are usually asymptomatic apart from the jaundice and investigations reveal isolated indirect hyperbilirubinemia. Genetic testing of the UGT1A1 gene for mutations is the definitive diagnostic tool which is not available everywhere. It can be alternatively diagnosed by evaluating the response to phenobarbitone in terms of fall in bilirubin level. Here, we report one such rare case.Faridpur Med. Coll. J. Jan 2020;15(1): 43-45